Analisis Kapasitas Drainase Jalan BTN Lago Permai Kota Pangkalan Kerinci Kabupaten Pelalawan - Lessy Maretha; Rinaldi Rinaldi; Mudjiatko Mudjiatko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The effect of residential areas development in the city of Pangkalan Kerinci causing a land conversion thus, increasing of surface waters flow due to rain. Surface runoff caused a flood inundation in Jalan Permai BTN Lago. Therefore we need an analyz to reduce flood inundation by analyzing the capacity of drainage channels ranging from the most upstream channel to the final disposal site gas pipeline passing through the country. The existing drainage channels compared with the discharge channel plan with return period of 5 years. Results of comparative analysis is 17.48% drainage channel had width modified (b), 35.92% had modified the width (b) and height (h), 44.66% of drainage channels are not modified, and 1.94% are the new channel. The most downstream channel passes through a gas pipeline that takes cross-sectional modification into reservoir. It required help of a pump for pumping water from the reservoir into the exhaust channel / outlet. reservoir accept 5.63 m3 / sec discharge for the return period of 5 years. Modified existing drainage channels into reservoir withsize (2m x 5m x 230m) using a pump with a capacity of 5 m3 / sec.Keywords: drainage systems, capacity, dimensions